"Moving on" through the locked ward system for women with intellectual disabilities. Issue 4 (5th April 2019) - Fish, Rebecca; Morgan, Hannah
Abstract: Background: The move to community support for all people with intellectual disabilities is an aspiration with international significance. In this article, we draw on rich accounts from women with intellectual disabilities detained under the Mental Health Act (E&W) 1983 and staff at an National Health Service secure setting in England to explore how "moving on" is defined and perceived. Methods: The study reports on an ethnographic study using the field‐notes and the 26 semi‐structured interviews with detained women and staff on three wards. Results: We first explore staff conceptions of moving on, which include behavioural change and utilizing coping strategies. Then, we discuss the areas of analysis that women discussed: taking back responsibility, success in arranged relationships, acceptance of regime and resistance to progression. Conclusion: The concepts of moving on were not determined by the women but by the service. We recommend further research which explores women's own rehabilitation requirements.